Two new feather mites of the genus Proctophyllodes Robin (Acari formes: Proctophyllodinae) from passerines in Brazil - Pedroso, Luiz Gustavo A. [UNESP]; Hernandes, Fabio Akashi (Systematic and Applied Acarology Society, 2021)
Proctophyllodes Robin (Proctophyllodidae: Proctophyllodinae) is a widely distributed feather mite genus, which most species show high level of specificity to their bird hosts. We describe two new species of this genus from passerines commonly found in urban environments in Brazil: Proctophyllodes molothrussp. nov. from the Shiny Cowbird Molothrus bonariensis (Gmelin) (Icteridae), and P. carmenmirandaesp. nov. from the Rufous-collared Sparrow Zonotrichia capensis (Statius Müller) (Passerellidae). The former is similar to P. egglestoni Spory and differs from it in having a unique shape of opisthosomal lobes in females; P. carmenmirandae is closer to P. tiaris Atyeo & Braasch and differs in having a relatively longer adeagus in males and setae h1 situated on soft tegument between hysteronotal and lobar shields in females.
Keywords: Analgoidea; Feather mites; host-association; Icteridae; Molothrus bonariensis; Passerellidae; symbionts; Systematics; Zonotrichia capensis